Always Open, Seven-Eleven: Education Targeting Healthier Food Choices in a High Convenience Store Density Area in Taipei - Dai, Chia-Liang; Chen, Ching-Ying; Wang, Ziying; Chang, Cheng-Liang (International Journal of Child Health and Nutrition, 2022)
To enhance children's health, the promotion of nutrition literacy in school is vital as it helps prevent the development of health conditions and diseases and maintain healthy lifestyles. Taiwan features the top highest ratio of convenience stores per population density. Convenience stores, an increasingly popular dining place, were linked to the development of eating behavior and body weight issues in children. An eight-week classroom-based nutrition intervention, employing the Traffic Light Diet as a framework, targeting children's perception of and intention to visit the convenience store was implemented. The study conducted a quasi-experimental pretest-posttest research design with a comparison group. A total of 49 students participated in the study, with 25 in the intervention and 24 in the comparison group. Data were collected by utilizing surveys, interviews, and observations. The study's findings demonstrated the positive trajectory of the impact of this intervention on increasing food-and-nutrition-related knowledge and improving healthier diet choices at convenience stores among children. One main theme was identified in coding interviews: parent involvement in meal preparation may reduce convenience store use and increase consumption of vegetables among children. Assessing the influence of parental support for healthy dietary choices, eating nutritious foods at home, and involving the family in meal preparation is an area for future research.